AI-Driven Learning Model for Early Childhood Cognitive and Communication Development: An Education for Sustainable Development Approach - Selfi Lailiyatul Iftitah; Ardhana Reswari; Danang Prastyo; Lia Fitriana Wahyuni (IAIN Madura, 2026)
Advances in artificial intelligence have completely transformed the landscape of early childhood education; however, research that comprehensively integrates artificial intelligence, cognitive development, communication skills, and the Education for Sustainable Development framework at the early childhood education level remains very limited. These limitations underscore the need for research that examines the direct experiences of teachers and children in artificial intelligence-based learning processes in a thorough and contextual manner. This study aims to identify an artificial intelligence-based learning model that optimizes the cognitive development and communication skills of young children within the framework of Education for Sustainable Development at Al Azhar Kindergarten in Pamekasan. The study employed a qualitative approach with a phenomenological design using Interpretative Phenomenological Analysis, involving a school principal, three classroom teachers, and twenty students as informants. Data collection techniques included participant observation, in-depth interviews, and a review of instructional documents, conducted from January through March 2026. The research findings revealed four main themes: teachers’ pedagogical adaptation, improvements in children’s logical reasoning, the development of children’s verbal communication skills, and the alignment of the learning model with the principles of inclusivity and future-oriented approaches within the framework of Education for Sustainable Development. This study confirms that artificial intelligence-based learning models are suitable for implementation in early childhood education as a strategic tool for achieving Sustainable Development Goal 4.